The IMPLEMENTATION OF THERAPEUTIC GROUP THERAPY IN PREGNANT WOMEN IN EFFORTS TO ACHIEVE OPTIMUM CHILD DEVELOPMENT IN WORKING AREA OF PEKAN HERAN PUBLIC HEALTH CENTER, INDRAGIRI HULU DISTRICT - Alice Rosy (Poltekkes Kemenkes Riau, 2022)
One of the factors that influence the case of stunting in children is the mother's parenting manner. This parenting manner is not only when the baby is born, but since the baby is still in the womb of the mother, which in turn can affect the child's growth and development. In an effort to prepare a physically, psychologically and socially healthy pregnancy and fetus both in the womb and in the future. a group of therapeutic therapy was administered to pregnant women. Although there have been efforts to improve maternal health through various government programs, these efforts have only touched on the physical aspects and have not yet addressed the efforts to improve the psychosocial and psychological aspects of pregnant women. This is important because cognitive and emotional growth and development of children are closely related to maternal psychological problems during pregnancy. Many studies have reported that the case of depression in pregnant and lactating women has resulted in delays in cognitive and emotional development of children at various ages, so this intervention is important. Therapeutic Group Therapy (TKT) in pregnant women is important in the hope that pregnant women can adapt well to any changes in pregnancy, especially psychological changes and are able to stimulate the development of the fetus they contain. This TKT can be followed by all 11 participants with a value of> 2 meaning that participants can continue until all sessions at this TKT are finished, but they must always be monitored during its implementation and involve local midwives in this activity so that participants are able to independently care for babies and also able to carry out the role of the mother proportionally, after giving birth later.